EVALUATION OF RENAL PROTECTIVE ACTIVITY OF ADHATODA ZEYLANICA (MEDIC) LEAVES EXTRACT IN WISTAR RATS - Kumar, Arunachalam; N., Suchetha Kumari; D'Souza, Prima; Bhargavan, Divya (Journal of Health and Allied Sciences NU, 2013)
The kidney is especially a susceptible organ to toxic injuries by drugs and toxin, because of a high blood supply and the presence of cellular transport systems that cause accumulation of these compounds within the nephron epithelial cells. Glomerular, tubular and interstitial cells frequently encounter significant concentrations of medications and their metabolites, which can induce changes in kidney function and structure. Renal toxicity can be a result of hemodynamic changes, direct injury to cells and tissue, inflammatory tissue injury and/or obstruction of renal excretion.Gentamicin is potent broad spectrum antibiotic therapeutic agent used in a number of infective conditions. Because of the obvious mediation of Reactive Oxygen Species in Gentamicin induced renal damage. Several antioxidant agents have been used to block Gentamicin nephrotoxicity.There is a proven converse relationship between the consumption of antioxidant rich plants incidence of human diseases. A primary goal of this study is to present the scientific evidence for the use of common herb Adhatoda zeylanica as supplementary in the gentamicin treated acute renal failure (ARF) subjects. The beneficial effect of A. Zeylanica against gentamicin nephrotoxicity, possibly depends on its ability to scavenge the gentamicin induced free radicals.This study demonstrates the effectiveness of the extract improved with the polarity of the solvents over a period of 10 days and the plant has the potential to ameliorate Gentamicin nephrotoxicity.
Keywords: nephrotoxicity; Adhatoda zeylanica; gentamicin; free radicals; histopathology